The role of anti-phospholipid antibodies in autoimmune reproductive failure. Issue 5 (May 2016) - Pantham, Priyadarshini; Abrahams, Vikki M; Chamley, Lawrence W
Abstract: Anti-phospholipid antibodies (aPL) are autoantibodies that are associated with thrombosis and a range of pregnancy complications including recurrent pregnancy loss and pre-eclampsia. The three clinically relevant, well-characterized aPL are anti-cardiolipin antibodies, lupus anticoagulant and anti-beta-2-glycoprotein I (β2 GPI) antibodies. aPL do not bind directly to phospholipids but instead bind to a plasma-binding 'cofactor'. The most extensively studied cofactor is β2 GPI, whose role in pregnancy is not fully elucidated. Although the pathogenicity of aPL in recurrent pregnancy loss is well established in humans and animal models, the association of aPL with infertility does not appear to be causative. aPL may exert their detrimental effects during pregnancy by directly binding trophoblast cells of the placenta, altering trophoblast signalling, proliferation, invasion and secretion of hormones and cytokines, and by increasing apoptosis. Heparin is commonly used to treat pregnant women with aPL; however, as thrombotic events do not occur in the placentae of all women with aPL, it may exert a protective effect by preventing the binding of aPL to β2 GPI or by acting through non-thrombotic pathways. The aim of this review is to present evidence summarizing the current understanding of this field.